SEX MORALITY AS THE ESSENCE OF KAFA’AH IN MARRIAGE ACCORDING TO KITABUN NIKAH AL-BANJARY AND THE COMMUNITY OF BANJAR - Hafidzi, Anwar; Hasan, Ahmadi; Muzainah, Gusti; al-Amruzi, Fahmi (Jurnal Fiqh, 2023)
The purpose of this study is to ascertain the opinions of Shaykh Arsyad al-Banjary regarding the significance of sexual morality as the foundation of kafa’ah, both before and after marriage, the trend inclination of sexual orientation of household residents in Banjar, South Kalimantan. The al-Banjari Kitabun Nikah chapter on domestic sex morals, which was composed in the 17th century in Malay-Jawi was studied. Complementary information from three married participants was used in determining the ethical restrictions on sex in marriage as part of kafa’ah (eligibility at marriage). Having healthy children is one of the objectives of a marriage. The husband and wife must engage in sexual activity for this to happen. This study shows that having sexual ability is a key component of marriage, and that if one wants to get married, one should find out about one’s sexual ability from a medical professional. Many people, however, believe that sex is always about having fun. To ensure that neither partner feels disadvantaged, sexual encounters must be carried out on the basis of mutual needs and liking.